ANALISIS KORELASI PENGEMBANGAN SUMBER DAYA MANUSIA DENGAN KINERJA PEGAWAI (Studi Pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Kutai Barat) - Susana, Iling (PREDIKSI, 2015)
ABSTRACTÂ This study aims to determine whether the Human Resources Development has a positive correlation to the Employee Performance Management Agency Finance and Asset Kutai Barat.The results showed that there is a positive and significant relationship between the variables of Human Resources Development with variable Employee Performance Board Finance and Asset Management District West Kutai. It can be seen from the results of statistical test in which the correlation coefficient (r) is equal to 0.725, which means the relationship is positive, because the value of the correlation coefficient in the prices of critical r = 0.413.Meanwhile if the results are compared with the table provide guidelines for the interpretation of Product Moment Correlation Coefficient, as stated in Chapter III, the results of these calculations are at intervals of 0.60 to 0.799, which means that there is a strong relationship between the variables with the Human Resources Development Employee Performance variables.